The wootton bassett mud spings (Wiltshire, U.K.): an unusual Largerstatten for jurassic foraminifera - Hart, Malcolm B.; Henderson, Andrew S.; Frayling, Timothy (Anuário do Instituto de Geociências, 2006)
Abstract